Midaortic Syndrome: 30 Year Experience with Medical, Endovascular and Surgical Management - Porras, Diego (2013)
BACKGROUND: Midaortic syndrome is often associated with refractory hypertension. Our aim was to better understand the short and medium-term outcomes in this patient population utilizing a multidisciplinary management approach. METHODS: We conducted a review of patients with midaortic syndrome treated at our institution over the past 30 years. RESULTS: Fifty-three patients presented at a median age of 6.7 (birth – 28.7) years. Thirty-five patients (66%) underwent invasive management (percutaneous techniques: 21; surgical techniques: 5; both: 9). Percutaneous interventions were acutely successful in decreasing the gradient across the obstruction and degree of luminal stenosis. However, freedom from reintervention was 58% at 1 year and 33% at 5 years. Freedom from reintervention after a surgical procedure was longer: 83% at 1 year and 72% at 10 years. At most recent follow-up, the majority of patients (69%) were normotensive. The median duration between time of presentation and achievement of blood pressure control was 5.7 (0.4 – 21.1) years. The median number of anti-hypertensive medications was 1 (0 – 5). CONCLUSIONS: A multidisciplinary management strategy, which couples comprehensive medical management with catheter-based and surgical interventions, can lead to adequate blood pressure control and preservation of end-organ function in patients with midaortic syndrome.